2001
DOI: 10.1093/carcin/22.5.751
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase activation and p53 mutations in urethane-induced A/J mouse lung tumor development

Abstract: The mouse telomerase holoenzyme, which synthesizes telomeric DNA de novo, is a ribonucleoprotein complex that includes the mouse telomerase RNA component (mTERC), mouse telomerase-associated protein (mTEP1) and mouse telomerase reverse transcriptase (mTERT). To determine the role of telomerase in urethane-induced lung tumorigenesis in A/J mice we examined telomerase activity and the expression of each telomerase subunit in 20 tumor samples, harvested at 16, 28, 40 and 50 weeks after urethane treatment. The tel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 4 publications
2
11
0
2
Order By: Relevance
“…2003). Similar to the results obtained by Ohno et al. (2001) in urethane‐induced lung tumour in A/J mice, we found upregulation of mouse TERT mRNA in both models of CRC.…”
Section: Discussionsupporting
confidence: 90%
“…2003). Similar to the results obtained by Ohno et al. (2001) in urethane‐induced lung tumour in A/J mice, we found upregulation of mouse TERT mRNA in both models of CRC.…”
Section: Discussionsupporting
confidence: 90%
“…The p53 ‐specific mutation has been reported to be involved in telomerase activation (Ueda et al ., ). On the contrary, studies on mouse tumour lung development (Ohno et al ., ) and human breast cancer (Roos et al ., ) showed no correlation between telomerase activity and p53 mutations but it was associated with p53 protein accumulation (Roos et al ., ). In this study, telomerase activity in ASCs showed no significant changes in the relative telomerase activity (RTA) at P5, P10, P15 and P20.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of hTERT and mTERT mRNAs was analyzed by reverse transcription (RT)-PCR and real-time RT-PCR as described previously (33,39). Briefly, total RNA was isolated from the cells using an RNeasy Mini Kit (QIAGEN) according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
“…PCR used 30 s at 94°C, 30 s at 60°C, and 30 s 72°C for hTERT and 30 s at 94°C, 30 s at 55°C, and 30 s at 72°C for mTERT, with 28 cycles for conventional PCR and 40 cycles for real-time PCR. The efficiency of cDNA synthesis from each sample was estimated by PCR for human glyceraldehyde-3-phosphate dehydrogenase or mouse ␤-actin as described previously (33,39).…”
Section: Methodsmentioning
confidence: 99%